Challenges in delivering computed tomography coronary angiography as the first-line test for stable chest pain. Issue 11 (14th November 2017) - Dreisbach, John G; Nicol, Edward D; Roobottom, Carl A; Padley, Simon; Roditi, Giles
Abstract : Objective: The National Institute for Health and Care Excellence (NICE) clinical guidelines 'chest pain of recent onset: assessment and diagnosis' (update 2016) state CT coronary angiography (CTCA) should be offered as the first-line investigation for patients with stable chest pain. However, the current provision in the UK is unknown. We aimed to evaluate this and estimate the requirements for full implementation of the guidelines including geographical variation. Ancillary aims included surveying the number of CTCA-capable scanners and accredited practitioners in the UK. Methods: The number of CTCA scans performed annually was surveyed across the National Health Service (NHS). The number of percutaneous coronary interventions performed for stable angina in the NHS in 2015 was applied to a model based on SCOT-HEART (CTCA in patients with suspected angina due to coronary heart disease: an open-label, parallel-group, multicentre trial) data to estimate the requirement for CTCA, for full guideline implementation. Details of CTCA-capable scanners were obtained from manufacturers and formally accredited practitioner details from professional societies. Results: An estimated 42 340 CTCAs are currently performed annually in the UK. We estimate that 350 000 would be required to fully implement the guidelines. 304 CTCA-capable scanners and 198 accredited practitioners were identified. A marked geographical variation between health regions was observed. Conclusions: This study provides insight into the scale of increase in the provision of CTCA required to fully implement the updated NICE guidelines. A small specialist workforce and limited number of CTCA-capable scanners may present challenges to service expansion.